Proximal and Distal Regions of Pathogenic Th17 Related Chromatin Loci Are Sequentially Accessible During Pathogenicity of Th17 - Hu, Luni; Zhao, Xingyu; Li, Peng; Zeng, Yanyu; Zhang, Yime; Shen, Yang; Wang, Yukai; Sun, Xiaolin; Lai, Binbin; Zhong, Chao (Frontiers in Immunology, 2022)
Pathogenic Th17, featured by their production of pro-inflammatory cytokines, are considered as a key player in most autoimmune diseases. The transcriptome of them is obviously distinct from that of conventional regulatory Th17. However, chromatin accessibility of the two Th17 groups have not been comprehensively compared yet. Here, we found that their specific chromatin accessible sites (ChARs) significantly correlated with the expression of related genes, indicating that they might engage in the regulation of these genes. Indeed, pathogenic Th17 specific ChARs (patho-ChARs) exhibited a significant distribution preference in TSS-proximal region. We further filtered the patho-ChARs based on their conservation among mammalians or their concordance with the expression of their related genes. In either situation, the filtered patho-ChARs also showed the preference to TSS-proximal region. Enrichment of expression concordant patho-ChAR related genes suggested that they might involve in pathogenicity of Th17. Thus, we also examined all ChARs of patho-ChAR related genes, and defined an opening ChAR set according to their changes in the Th17 to Th1 switch. Interestingly, these opening ChARs displayed a sequential accessibility change from TSS-proximal region to TSS-distal region. Meanwhile, a group of patho-TFs (transcription factors) were identified based on the appearance of their binding motifs in the opening ChARs. Consistently, some of them also displayed a similar preference in binding to the TSS-proximal region. Single-cell transcriptome analysis further confirmed that these patho-TFs were involved in the generation of pathogenic Th17. Therefore, our results shed light on a new regulatory mechanism underlying the generation of pathogenic Th17, which is worth to be considered for autoimmune disease therapy.